Subjectivity and the "Human Sciences" in Wilhelm Dilthey - Monteagudo, Cecilia (1992)
Within the framework of some of Dilthey's themes such as historicity, finitude and the ineffability of all human productions, the A. approaches the problem of Subjectivity in relation to the Human Sciences (Geisteswissenschaften) which, conceived as forms of self-reflection of historical life itself, put in evidence a Subject compelled to redefine its cognitive possibilities. This task leads Dilthey to a hermeneutical proposal, the main value of which lies in not having eluded facticity and temporality proper to life, and in having proposed them as domains where all intellectual activity finds its limits and the openness to new possibilities of sense.